2021
DOI: 10.1002/solr.202100548
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and Omnidirectional Antireflection Surfaces Based on Deep Subwavelength Features for Harvesting of the Solar Energy

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/solr.202100548.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The Bosch process allows for accurate tuning of the DSSS geometry (e.g., H dsss and W dsss ) by management of the various dry etch parameters. In this way, a deterministic fabrication of DSSS is possible. ,, One main concern in DSSS arrays is the increase in surface area which will result in higher surface recombination and lower photovoltage performance. Recently, surface passivation techniques demonstrated efficient surface passivation to provide surface recombination values as low as 10 cm/s which can address the concern of higher surface area .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bosch process allows for accurate tuning of the DSSS geometry (e.g., H dsss and W dsss ) by management of the various dry etch parameters. In this way, a deterministic fabrication of DSSS is possible. ,, One main concern in DSSS arrays is the increase in surface area which will result in higher surface recombination and lower photovoltage performance. Recently, surface passivation techniques demonstrated efficient surface passivation to provide surface recombination values as low as 10 cm/s which can address the concern of higher surface area .…”
Section: Discussionmentioning
confidence: 99%
“…The 4 n 2 limit is based on geometrical optics, and it pursues surface decoration of both sides of the thin film in order to increase the optical power in the film. More recently, it was suggested and demonstrated that the 4 n 2 limit can be exceeded if surface decoration with subwavelength structures is employed. Various light trapping mechanisms were identified to produce broadband absorption enhancement of the sun power with surface subwavelength arrays: low optical impedance using arrays of nanocones and black silicon, forward scattering by surface Mie resonators, increase in local density of states, excitations of Bloch modes, light trapping driven by light concentration and the utilization of nanolenses and light funnels, excitations of localized Mie resonances, ,, and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A metascreen is a remarkable optical material that possesses the ability to manipulate the properties of electromagnetic (EM) waves by selectively transmitting, reflecting, and absorbing specific wavelengths. Its unique characteristics have spurred research and development in various exciting fields, including solar power systems, [ 1–4 ] telecommunications, [ 5–8 ] energy, [ 9–11 ] sensors, [ 12–14 ] and camouflage. [ 15–22 ] Many researchers have explored the applications of metamaterials using various principles, such as intrinsic materials, [ 23–25 ] optical cavity, [ 11,26–30 ] and particle resonance.…”
Section: Introductionmentioning
confidence: 99%
“…A novel and efficient surface-trapping technology has attracted the attention of researchers. Wang et al used an effective light-coupling method, in which a periodic quasi-hemisphere micro-nanostructure was prepared on the front glass surface to improve the property in thin-membrane solar cells [30][31][32]. This process does not require a change in the processing technology of thin-film solar cells with a flat glass substrate.…”
Section: Introductionmentioning
confidence: 99%